KEMAMPUAN INTELEKTUAL, PENGEMBANGAN KARIR DAN WORK ENGAGEMENT TERHADAP KINERJA KARYAWAN PT. BPR EKADHARMA BHINARAHARJA GORANGGARENG KABUPATEN MAGETAN - Kusniawati, Yeni; Kristiyana, Naning; Widhianingrum, Wahna (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The purpose of this study was to determine whether there is an influence between intellectual ability, career development and work engagement on employee performance at PT. BPR Ekadharma Bhinaraharja Goranggareng, Magetan Regency. Data collection techniques using questionnaires.”The sample used in this study was 76 respondents. The analysis technique used in this study uses multiple linear regression analysis using data instrument tests, classic assumption tests, multiple regression analysis, and hypothesis testing using the IMB SPSS statistical analysis tool 22. From the t test it shows that intellectual abilities have an effect positive on employee performance. Career development has a positive effect on employee performance. Work engagement has a positive and significant effect on employee performance at PT. BPR Ekadharma Bhinaraharja Goranggareng, Magetan Regency”. The results of the F test show that intellectual ability, career development and work engagement have a simultaneous effect on employee performance at PT. BPR Ekadharma Bhinaraharja Goranggareng, Magetan Regency